2021
DOI: 10.3390/ani11072090
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Genetic Variants within the Goat A-Kinase Anchoring Protein 12 (AKAP12) Gene and Their Effects on Growth Traits

Abstract: The A-kinase anchoring protein 12 gene (AKAP12) is a scaffold protein, which can target multiple signal transduction effectors, can promote mitosis and cytokinesis and plays an important role in the regulation of growth and development. In our previous study, P1–7 bp (intron 3) and P2–13 bp (3′UTR) indels within the AKAP12 gene significantly influenced AKAP12 gene expression. Therefore, this study aimed to identify the association between these two genetic variations and growth-related traits in Shaanbei white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…45,46 AKAP12, a scaffolding protein gene affecting multiple signaling effectors, has been shown to play a significant role in regulating growth and development. 47 Studies have shown that it is related to inflammation, however, the underlying mechanism is not clear. 48 osteogenesis-inducing conditions, which is consistent with the results of bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 AKAP12, a scaffolding protein gene affecting multiple signaling effectors, has been shown to play a significant role in regulating growth and development. 47 Studies have shown that it is related to inflammation, however, the underlying mechanism is not clear. 48 osteogenesis-inducing conditions, which is consistent with the results of bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…PLAT, an ECM remodeling enzyme, has been observed to function during the recovery phase of colitis 45,46 . AKAP12, a scaffolding protein gene affecting multiple signaling effectors, has been shown to play a significant role in regulating growth and development 47 . Studies have shown that it is related to inflammation, however, the underlying mechanism is not clear 48 .…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most important economic traits in large-scale breeding, goat reproductive traits account for a large proportion of the overall income of breeders. However, the low heritability of reproductive traits, the long cycle, the slow breeding progress and the complex relationship with growth traits are the main reasons for the economic disadvantages of goat breeding [ 34 , 35 ]. With the development of biotechnology, marker-assisted selection (MAS) has been widely used in goat breeding to rapidly enhance goat reproductive performance.…”
Section: Discussionmentioning
confidence: 99%
“…InDel variants in introns should not be ignored; many InDels located in intron regions of genes significantly affect animal production traits. For example, variants in the introns of SNX29 [ 16 ], IGF2BP [ 14 ], and AKAP12 [ 44 ] significantly affect body traits in animals. Similar to the results of the previous studies, the three InDel loci in this trial were also located in introns, and they significantly correlated with body traits.…”
Section: Discussionmentioning
confidence: 99%